Ethical dimension inside health care institutions: the ethics committees for clinical practice. - Viafora, Corrado (Medicina e Morale, 2004)
This essay proposes a recognition of the institutionalisation process of the Ethics Committees for clinical practice. According to the international trends the main functions of these Committees are: a. ethical analysis of clinical case; b. development of institutional guidelines; c. organisation of educational programs for health professionals and community. The recognition considers the north-american perspective, signed by the evolution from the advocacy paradigm to the organisation paradigm; the European perspective, oriented to create both committees as public forum for debating ethical issues in the health care institutions, and committees as structures for helping the decision- making process; the Italian perspective, still signed by a situation of fragility and uncertainty. Since the institution of Ethics Committees for clinical practice involves important potentialities in renewing the ethical dimension in the health care institution, the essay identifies and discuss three models in which these potentialities could be realised. The first model is developed in a professional perspective, for helping health professional dealing with increasingly complex ethical problems and for creating a space for the integration of different professions. A second model is developed in an organizational perspective, for implementing institutional guidelines and for sensitising health care professionals to the ethical dimension of their work more than to involve them more directly in the institutional responsibility. A third model is developed in a public perspective, for creating occasions of public debate and a real communication between the society and health care institutions. 938